Optimization of interfacial bonding properties between thermoplastic liners and carbon fiber‐reinforced composites by atmospheric‐pressure plasma and failure mechanism study. Issue 4 (21st February 2023) - Qi, Liangliang; Min, Wei; Gao, Ruize; Li, Zhiqi; Yu, Muhuo; Sun, Zeyu
Abstract: Weak interfacial bonding properties between thermoplastic liners and carbon fiber‐reinforced composites (CFRP) can easily lead to debonding failure, which is a major challenge in development of type IV composite hydrogen storage vessels. We optimized Box–Behnken design atmospheric‐pressure plasma process parameters for maximizing interfacial bonding properties between thermoplastic liner (PA11 liner) and CFRP using Design‐Expert software. From various designs, plasma process parameters, including time ( t ), nozzle‐to‐specimen distance ( d ) and gas flow rate ( r ) of treatment were selected for optimization to assess the effects of their interactions on climbing drum peel (CDP), flatwise tensile (FWT) and asymmetric double cantilever beams (ADCB). The CDP strength, FWT strength and strain energy release rate ( G ADCB ) of untreated samples were 4.2 N·mm/mm, 0.26 MPa and 87.2 J/m 2, respectively. After the plasma treatment, optimum process parameters of t = 200 s, d = 12.5 mm, and r = 700 L/h were used to achieve 33.8 N·mm/mm, 2.97 MPa and 1008.4 J/m 2, respectively, which were 8.0, 11.4 and 11.6 times that of untreated PA11 surface, respectively. This method has the potential for guiding thermoplastic liner surface treatment of type IV hydrogen storage vessels before winding. Abstract :